Pengaruh Transparansi dan Akuntabilitas Pengelolaan Zakat, Infaq, Shodaqoh Terhadap Minta Masyarakat Berdonasi di Lazismu Kota Medan - Muhammad Sayful Arifin Ritonga (Yayasan Rahmat Islamiyah, 2021)
Zakat management is carried out with various management mechanisms. However, some issues are still found in its management. There is distrust by zakat payers (Muzakki) due to the lack of transparency in reports on the use of zakat funds by the Zakat Management Organization. The low level of public trust in LAZ makes many people choose to channel it through zakat collection institutions that do not yet have official permission to manage zakat. Where the population used was the number of muzakki from 2018 to 2022, namely 464 populations. In this study, the sampling technique used by the researcher was saturated sampling. as many as 85 samples. This research uses multiple linear regression analysis technique. In this study, transparency has an effect on public interest as seen from the t count t table (7.838>1.663) and the significant level is smaller than 0.05 (0.000<0.05). In this study, accountability has an effect on public interest, as can be seen from the t count t table (3.269>1.663) and the significant level is smaller than 0.05 (0.002 <0.05). In this study, transparency and accountability affect the public interest. Fcount Ftable (88.629>3.11) and a significant level which is smaller than 0.05 (0.000<0.05), the coefficient of determination shows an R Square value of 0.684 meaning 68.4%. the simultaneous existence of transparency and accountability affects public interest in donating to Lazismu Medan city by 68.4%, and the remaining 32.6% is influenced by other variables outside of this research variable.